Formulação para determinação da força cortante resistente de flambagem do montante de alma em vigas celulares de aço - Lucas Figueiredo Grilo (2018)
This research presents a study about the structural behavior of cellular steel beams, focused on beams subjected to web-post buckling. The main objectives of this study are to analyze the structural behavior and propose a new formulation to calculate the shear resistance of cellular beams subjected to this phenomenon, based on laboratory tests and numerical analysis. The state of the art of cellular beams subjected to web-post buckling design is shown, and the divergences between the existing formulations between each other and between experimental results are presented. Series of laboratory tests of cellular beams are performed in this work, with real size beams subjected to web-post buckling and Vierendeel mechanism. In these experiments, vertical and lateral displacements are measured, as well as web-post deformations. The steel mechanical properties of these beams are determined by tensile testing. The influence of shape and magnitude of the web-post initial imperfection on shear resistance was numerically analyzed. Based on this analysis and experimental results, a numerical model was proposed, developed in ABAQUS software, to perform parametric analysis. From these numerical models, processing of 597 cases, a new formulation to determine the shear resistance in cellular beams subjected to web-post buckling was proposed, based on the determination of resistance curves. The proposed formulation was verified in several situations of geometry and material properties, presenting compatible results with those obtained numerically, and showing more accuracy than those available in the literature